The cyclic relationship between environmental, social and governance (ESG) disclosure and corporate financial performance (CFP) in a regional economy - Aik, Nai Chiek (Tanjong Malim, 2021)
The cyclic relationship between environmental, social and governance (ESG) disclosure and corporate financial performance (CFP) in a regional economy by Aik, Nai Chiek